PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INTRACTION UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SD NEGERI 008 BONAI DARUSSALAM - Siti Jamilah; Rejeki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the improvement of student learning outcomes in Citizenship Education (PKn) through the implementation of problem-based learning models in the fourth grade of SD Negeri 008 Bonai Darussalam. This type of research is classified as classroom action research (CAR). The research was conducted in 2 cycles, with each cycle consisting of 2 meetings, and in each meeting there are 4 stages: planning, action, observation, and reflection. Data collection techniques were carried out through observation and tests. The subjects of this research are 25 students from Class IV A of SD Negeri 008 Bonai Darussalam. The data analysis technique used both qualitative and quantitative analysis. The results of the study indicate that the implementation of the Problem Based Instruction (PBI) model can improve the learning outcomes of fourth-grade students at SD Negeri 008 Bonai Darussalam. In the first cycle, student engagement was still low with a completeness of only 48% in the first meeting, which increased to 64% in the second meeting. In the second cycle, there was a significant improvement with the learning completeness reaching 76% in the first meeting and 84% in the second meeting. The activities of both students and teachers were also categorized as very good. Therefore, the PBI model has been proven to be effective in enhancing learning outcomes and student engagement in Social Studies.